Contribution of Professional Teachers to the Local Economy of Cebu City, Philippines - Almaden, Antoniette; Herbieto, Jan Roel; Velasco, Mila Mae (JPAIR Multidisciplinary Research, 2022)
A yoga teacher deems professional when remuneration is generated from teaching and guiding students on the path of Yoga, including the practices of pranayama, meditation, and asana. This study intends to determine whether professional yoga teachers contribute an economic value in terms of employment and income tax to the local economy of Cebu. This study used the quantitative research method. About ten professional yoga teachers certified by Yoga Alliance, Vinyasa Yoga Academy, Mudra School, and World Peace Yoga School participated in the online survey. Economic evaluation tools such as break-even and cost- benefit analysis were applied to determine the cash flows generated between the investment (cost) incurred from acquiring the certification of a registered yoga teacher (RYT) and the earnings (benefit) generated from yoga classes conducted. It was discovered that a registered yoga teacher earns an average pay of Php165 or USD 2.9216 per hour per student derived from the 60/40 profit-sharing principle. Given the fixed cost of acquiring the RYT-200 certification and the estimated monthly earnings, part-time professional yoga teachers would need at least six months, and full-time would need at least two months to break even. The cost-benefit ratio indicates that the cash flows generated were viable since CBR >1; for each 1-peso value in the teacher’s training certification and equipment costs, 2.07 peso benefits for part-time and 6.70 pesos for full-time were generated. Therefore, professional yoga teachers were expected to create incremental economic value contributions to the local economy of Cebu.